Analysis of gene expansion and defense-related genes in Anacardiaceae family from an evolutionary aspect - Fan, Bing-Liang; Chen, Lin-Hua; Chen, Ling-Ling (Frontiers in Plant Science, 2025)
IntroductionThe Anacardiaceae family, encompassing economically and ecologically significant genera such as Rhus, Mangifera, and Pistacia, exhibits substantial genomic diversity and adaptive complexity. However, comparative genomic analysis and evolutionary insights into defense-related mechanisms within this family remain underexplored.Methods and resultsThis study employed a comprehensive phylogenomic, synteny, and gene family analysis across six Rhus species and three additional Anacardiaceae plants (Mangifera indica, Pistacia vera, and Anacardium occidentale). Our findings revealed distinct evolutionary trajectories: Mangifera/Anacardium underwent lineage-specific whole-genome duplications (WGDs) with chromosomal rearrangements, while Rhus/Pistacia retained only the ancestral gamma duplication. Pistacia’s genome expanded via transposable elements (TEs), whereas Rhus conserved chromosomal synteny despite accumulating TE-mediated structural variations. Some defense-related gene families, including WRKY transcription factors and nucleotide-binding leucine-rich repeat (NLR) genes, displayed substantial expansions and stress-responsive expression patterns, with 31 WRKY genes significantly upregulated during aphid infestation. NLRs clustered on chromosomes 4/12 showed positive selection signatures. Long terminal repeat retrotransposons exhibited Pleistocene-era activation bursts, potentially linked to climatic adaptation.DiscussionThis study unveils TE-mediated diversification as a key driver of Anacardiaceae evolution, complementing WGD-dependent strategies in tropical lineages. The identification of lineage-specific structural variations, dynamic TE activities, and clustered defense-related genes highlights adaptive trade-offs shaped by biotic stresses and the biogeographic history of Anacardiaceae species. This study lays the groundwork for leveraging these genomic resources to enhance stress resilience and adaptive potential in economically important Anacardiaceae crops.